Comparative Efficacy of Hybrid Capture 2 and Real-Time PCR in Detecting High-Risk HPV Genotypes for Cervical Cancer Screening - Aaysha Saifi; Sadaf Saifi (International Journal of Genetic Modifications and Recombinations, 2024)
Human papillomavirus (HPV) infection is a leading cause of cervical cancer, making early detection critical for effective prevention and treatment. Among the diagnostic methods available, Hybrid Capture 2 (HC2) and Real-Time Polymerase Chain Reaction (PCR) are widely used for detecting high-risk HPV genotypes, particularly HPV 16 and 18, which account for the majority of cervical cancer cases. This review aims to compare the efficacy of HC2 and Real-Time PCR in terms of sensitivity, specificity, and clinical utility in cervical cancer screening. HC2 is a well-established method that detects a broad range of HPV types, but it has notable limitations, such as cross-reactivity, which can lead to false positives. Its lower specificity makes it less reliable for distinguishing between high-risk and low-risk infections, resulting in unnecessary follow-ups and potential overtreatment. Conversely, Real-Time PCR offers higher specificity by directly amplifying and detecting viral DNA sequences, allowing for precise identification of high-risk HPV genotypes. This method also enables viral load quantification, providing additional clinical insights into the severity of infection and risk of disease progression. The comparative analysis suggests that while HC2 remains a useful tool for large-scale screening due to its ability to detect a wide range of HPV infections, Real-Time PCR is superior in terms of accuracy and clinical relevance. Its precise detection capabilities make it more effective for targeted screening and risk stratification in clinical settings. In conclusion, Real-Time PCR’s enhanced specificity and ability to reduce false positives present a significant advantage in improving cervical cancer screening outcomes, making it a more reliable tool for early detection and prevention strategies.
Keywords: DNA sequences; Human papillomavirus; Polymerase Chain Reaction (PCR); cervical cancer; transmitted infection